2020
DOI: 10.1155/2020/5706561
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of 2D Myocardial Strain for Epirubicin-Induced Cardiotoxicity

Abstract: Introduction. Although epirubicin has significantly improved outcome in breast cancer (BC) patients, it is responsible for myocardial dysfunction that affects patients’ quality of life. The use of 2D global longitudinal strain (GLS) has been reported to detect early myocardial dysfunction. The aim of this study was to evaluate how GLS changes can predict cardiotoxicity. Methods. We conducted a prospective study from March 2018 to March 2020 on 66 patients with no cardiovascular risk factors, who presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…Table 1 showed the demographic data and clinical characteristics of patients 16–59 . Cancer type, treatment, and imaging technique for each study are reported in Table 2 16–59 . Patient population ranged from 28 to 2625 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 showed the demographic data and clinical characteristics of patients 16–59 . Cancer type, treatment, and imaging technique for each study are reported in Table 2 16–59 . Patient population ranged from 28 to 2625 subjects.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 Cancer type, treatment, and imaging technique for each study are reported in Table 2 . 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , …”
Section: Resultsmentioning
confidence: 99%
“…However, the accuracy and sensitivity of LVEF in determining early myocardial injury is limited. By the time that LVEF values have decreased, cardiac injury has reached a stage which cannot be completely reversed (23,24). Two-dimensional GLS has previously been introduced as an index of chemotherapy-related cardiotoxicity in the 2016 position paper (3), and many studies have confirmed that the post-chemotherapy reduction in two-dimensional GLS compared with the pre-chemotherapy situation (25-27).…”
Section: Discussionmentioning
confidence: 99%
“…провели одно из первых исследований с использованием 2D-STE в 2015 г. и продемонстрировали, что данная методика чувствительна и специфична для субклинической дисфункции миокарда ЛЖ, ассоциированной с химиотерапией [23]. Исследования показали, что 2D STE более чувствительна, чем снижение ФВ ЛЖ, для ранней верификации субклинической дисфункции ЛЖ [24]. Также в наблюдательном исследовании проанализирована серийная оценка ССС до и после химиотерапии путем сравнения GLS с ФВ ЛЖ.…”
Section: результатыunclassified